UMKM RECOVERY STRATEGY IN MALANG CITY BASED ON DIGITAL MARKETING - Hasibuan, Razali Ade Syahputra; Asadiyah, Elia; Rahayu, Yayuk Sri (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 8 No 1 (2022): The 8th International Conference Of Islamic Economics And Business (ICONIES 2022), 2022)
This research was conducted to know the digital marketing strategies of UMKM actors in Malang City and to find out the impact of these strategies on the economic recovery of UMKM in Malang City. In this study, qualitative methods were used, which included this research in the type of exploratory qualitative research. The methods used are interviews, field observations, documentation and literature studies the object of research is UMKM in the culinary field in Malang City. The selected objects were taken from three sub-districts representing the entire city of Malang, the objects were Warung Bambu Mbak Yuyun in Lowokwaru District, Kedai Es Dempo 08 and Mie Bakar Celaket in Klojen District and Bubur Ayam Pak Awi in Blimbing District. The results of this study indicate that the perpetrators of UMKM in Malang City, are quite concerned with the development of technology and its use. The types of media used are Go-Food, Shopeefood, Grab Food, Instagram, Facebook ads and Whatsapp. The use of technology media as a strategy for digital marketing in Malang City has an impact on business culture, socio-culture, the rate of economic growth, Malang City government policies, the legal environment, and Islam.